Design and fabrication of portable book rack - Muhamad Harif, Ghani (2007)
ABSTRACT This project is about designing and fabricating the book rack that can store and keep the library equipment. It also has portability and easy to see from outside of the book rack. Another purposes this book rack give the user the easy to see inside the book rack with more directly. Numerous methods and process involve in this project for instance joining using welding process. The process to cut the sheet metal follows on their required dimension by using Turret Punch Machine. After all the process had been done, this Portable Book Rack project will help us to understand the fabrication and designing process that involved in this project.